2022
DOI: 10.3389/fpubh.2022.779498
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Experiences of Fear, Anxiety, Depression, and Changes in Sleep Pattern During the COVID-19 Pandemic Among Adults in Nigeria: A Cross-Sectional Study

Abstract: BackgroundMultiple facets of the pandemic can be a source of fear, depression, anxiety and can cause changes in sleep patterns. The aim of this study was to identify health profiles and the COVID-19 pandemic related factors associated with fear, depression, anxiety and changes in sleep pattern in adults in Nigeria.MethodsThe data for this analysis was extracted from a cross-sectional online survey that collected information about mental health and well-ness from a convenience sample of adults 18 years and abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Moreover, the respondents mainly experienced anxiety symptoms such as worrying too much, feeling anxious, annoyance and irritation, and feeling afraid due to the possibility of catching the coronavirus from patients attending rehabilitation services. Our findings paralleled the trends in other recent studies of the general population and healthcare professionals the Arab countries and around the world who reported having moderate to severe anxiety during the COVID-19 pandemic ( 10 , 20 23 , 29 31 , 34 , 45 ). Our results showed that neither the number of years of experience nor ages of the healthcare professionals had any influence on anxiety levels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the respondents mainly experienced anxiety symptoms such as worrying too much, feeling anxious, annoyance and irritation, and feeling afraid due to the possibility of catching the coronavirus from patients attending rehabilitation services. Our findings paralleled the trends in other recent studies of the general population and healthcare professionals the Arab countries and around the world who reported having moderate to severe anxiety during the COVID-19 pandemic ( 10 , 20 23 , 29 31 , 34 , 45 ). Our results showed that neither the number of years of experience nor ages of the healthcare professionals had any influence on anxiety levels.…”
Section: Discussionsupporting
confidence: 89%
“…Mallorquí-Bagué et als' review ( 8 ) highlights the link between anxiety and somatic symptoms. GAD is generally associated with developing somatic symptoms including headache, irritability, impaired concentration, sleep disturbance, fatigue, muscle and joint pain, and dizziness ( 8 , 10 13 ). COVID-19 research indicates that moderate to severe levels of anxiety due to the pandemic is associated with somatic symptoms such gastrointestinal ailments, fatigue, and difficulty sleeping ( 10 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid and extensive spread of the COVID-19 pandemic worldwide, besides the unprecedented changes in daily life, has left people alarmed and frightened [ 15 , 20 , 30 , 35 , 36 , 37 , 38 ]. Historically, there have been multiple outbreaks over the past years, such as the Severe Acute Respiratory Syndrome (SARS) epidemic, when moderate to severe post-traumatic stress symptoms were reported in the highly affected areas [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic provoked psychological distress among the general population [12][13][14][15][16][17][18]. It has been reported that 71% out of 4615 participants experienced psychological distress [19].…”
Section: Introductionmentioning
confidence: 99%